The significant other in professional path planning and readiness for scientific activity: The case of Russian students and postgraduates - M. V. Prokhorova; A. V. Savicheva; L. A. Kozlova; L. E. Semenova (Russian State Vocational Pedagogical University, 2023)
Introduction. The formation of professional plans by student youth is going on under the influence of significant others. The circle of significant others is suffering profound transformations in the conditions of changing cyber-technological paradigm, overflowing traditional family circle, friends, school masters (mentors), and needs clarification. The orientation and intensity of the impact of significant others on the modern educated youth's professional planning are not sufficiently studied. Solving the task of staff renewal in the Russian scientific sphere shows the necessity to reveal the roles of significant others in Russian students' and postgraduates' readiness to build a scientific career.Aim. In this research, the significant other is a really existing or imaginary person, who significantly influences student professional path planning, when a student identifies himself/herself with the significant other. The present research aims to reveal significant others, who influence professional plans of Russian students and postgraduates, and to establish the nature of its impact; to elicit the role of significant others in the students' and postgraduates' readiness to build a scientific career.Methodology and research methods. A three-part questionnaire was applied to collect data. In the first part, general information about the respondents was collected. The second part included three stages, which allowed the authors to identify three significant others, who influenced the respondents' professional plans, as well as to discover the nature of this influence. In the third part, the respondents reported about their readiness to build a scientific career. Primary data processing was carried out with the help of content-analysis. Secondary data processing involved descriptive statistics methods, non-parametric Pearson test, χ2, qualitative analysis. 1026 young people aged from 17 to 35, whose average age was 21, took part in the investigation. There were 951 students and 75 postgraduates from 10 Russian universities.Results. It was established that significant others influence the respondents' professional plans positively, neutrally and negatively. The positive impact prevails sharply over the neutral and negative ones. Over one-third of the students and postgraduates find it difficult to identify significant others. Among the significant others, there are both real people, who live now or have lived in the past, and imaginary characters. The real significant others can be subdivided into two groups: distant and close community. The role of significant other from distant community predominates over the influence of close community representatives.Scientific novelty. The authors designed the empirical model of significant others influencing the professional path planning. It was revealed that the students and postgraduates, who are not ready to become scientists, less often plan their professional paths under the influence of significant others from scientists and discoverers, than the other respondents. The hierarchical structures of students' and postgraduates' significant others have different readiness levels (from five to seven) to build a scientific career and have various component composition. In addition, a higher rank of scientists and discoverers as significant others in the sampling of future scientists should be noted.Practical significance. The obtained results, which deepen the understanding of the mechanism of professional identification and career decision-making, can be used in the practice of professional orientation and career counselling for young people. Since most students and postgraduates have difficulties in building professional plans or identify themselves with fictional characters or people involved in the public spheres like culture, art and mass media, the right choice of content and channels of professional propaganda can encourage young people to get a higher education and choose educational areas that are socially significant for the country.